2015
DOI: 10.1007/s00167-015-3796-0
|View full text |Cite
|
Sign up to set email alerts
|

The superficial medial collateral ligament is the primary medial restraint to knee laxity after cruciate-retaining or posterior-stabilised total knee arthroplasty: effects of implant type and partial release

Abstract: 17 PurposeAlthough soft-tissue contribution to stability of the intact knee has been studied 18 in relation to sports injuries, there is little data about their stabilising actions in the replaced 19 knee. The aim of this study was to quantify the contributions of medial soft-tissues to stability 20 following cruciate-retaining (CR) or posterior-stabilised (PS) total knee arthroplasty (TKA). 21Methods Using a robotic system, eight cadaveric knees were subjected to ±90N anterior-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The loads applied in this study were similar to other in vitro TKA studies, yielding similar laxities [2, 24]. Saeki et al [31] found that under 35 N AP force, 10 Nm VV, and 1.5 Nm IE torques, MCL release increased laxity in cruciate-retaining TKA knees throughout flexion.…”
Section: Discussionsupporting
confidence: 81%
“…The loads applied in this study were similar to other in vitro TKA studies, yielding similar laxities [2, 24]. Saeki et al [31] found that under 35 N AP force, 10 Nm VV, and 1.5 Nm IE torques, MCL release increased laxity in cruciate-retaining TKA knees throughout flexion.…”
Section: Discussionsupporting
confidence: 81%
“…The LCL was also found to contribute approximately 16% to resisting tibial anterior translation across flexion angles, a larger role than that previously found in native knees . This finding, along with a prior study into the contribution of medial soft tissues in TKA, suggests that in the absence of the anterior cruciate ligament the collaterals must provide a larger anterior restraint in implants with low conforming articular surfaces.…”
Section: Discussionmentioning
confidence: 48%
“…The knee was manually flexed 20 times to minimize soft tissue hysteresis and then tested in a robotic testing system previously described . The femur was fixed rigidly to the base of the robot and the tibia was mounted to the force/torque sensor on the end‐effector of the manipulator.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations